Risk Factors for Cerebrovascular Disease (Stroke) in Elderly - Anggraini, Debie; Haiga, Yuri; Sjaaf, Fidiariani (Scientific Journal, 2023)
The patophysiology of ischaemic stroke includes thrombosis and embolism. The risk factors are divided into two, namely risk factors that can be modified and risk factors that cannot be modified. Risk factors that cannot be modified are age, gender, race or ethnicity, family history of stroke and genetic factors. While risk factors that can be modified are hypertension, diabetes mellitus, hypercholesterolemia, smoking, atrial fibrillation, valvular heart disease, and carotid stenosis. The concept of ischemic penumbra is a basic reference in stroke treatment, because it is a manifestation of the presence of cellular structures of neurons that are still alive and may still be reversible if a rapid treatment is carried out. By understanding the pathogenesis of stroke through the mechanism of cell death, it is hoped that it can detect early and be used as a reference in the development of a policy to take preventive measures and early diagnosis in establishing the diagnosis of cerebrovascular disease